GAMBARAN SEMBILAN SIFAT UNGGUL PADA AGEN ASURANSI JIWA PT “X” JAKARTA - Stefani Virlia (Universitas Bunda Mulia, 2013)
Life insurance agents main role is to achieve sales targets policy. Success in achieving sales target is determined by the traits of the agent (Sutoyo, 2000). Traits can move and direct the person‟s behavior in dealing with other people in the environment (Allport, 1955). The traits that can support the success of agents in marketing insurance products expressed by Sukardi (1991, dalam Riyanti, 2009), which consists of an instrumental trait, the trait of achievement, the trait of social flexibility, hard work trait, self-confidence trait, risk-taking trait, the trait of self-control, innovative trait, and self-reliance trait. The purpose of this study is to describe the nine traits of life insurance agent PT X. Researcher used a quantitative approach, with an inventory of nine traits consist of 90 items. Researcher test the validity with the internal consistency method ( valid 80 items ) as well as reliability testing method with Cronbach alpha, with reliability coefficient of 0575-0789 on 87 agents. Data from 87 agencies were also taken researchers to address issues of research, analysis, and interpretation. Sampling was carried out using non-probability techniques are accidental sampling. The result showed that the dominant traits in life insurance agents are social flexibility trait, self-confidence, hard work, self-control, risk-taking, achivement, and instrumental trait. While the traits are less dominant in the life insurance agent are innovative and self-reliance trait. Keywords: life insurance agent, traits, description of nine traits